Systematic Review of The Impact Evaluation of Teacher Profession Education Programmes in Indonesia - Sari, Wiwin Rita; Komarudin, Komarudin; Badrujaman, Aip; Tola, Burhanuddin (IJBLE Scientific Publications Community Inc., 2023)
Education largely determines the progress of a nation and the development of the golden generation. Teachers play a strategic role in the educational process and must master core competencies to create innovative learning. The research methods used in literature review analysis articles play an important role in developing a solid framework and ensuring accurate and reliable analysis results. The results of the analysis show that The Teacher Profession Education Program (PPG) is a crucial step in improving the quality of teacher performance and attitudes towards the teaching profession. It plays an important role in identifying teachers' strengths and weaknesses, providing valuable feedback, and encouraging them to continue learning and developing their teaching skills. Evaluation of the impact of the PPG program is important to find out what benefits arise from participation in the program.